ETMR-18. TARGETING Lin28 IN ETMR WITH ODC1 INHIBITOR DFMO. (4th December 2020) - Goodyke, Austin; Kelly, Shannon; Zagorski, Joseph; VanSickle, Elizabeth; Maser, Tyler; Sortwell, Caryl; Kemp, Christopher; Nagulapally, Abhinav; Dykema, Karl; Saulnier-Sholler, Giselle
Abstract: Embryonal tumor with multilayered rosettes (ETMR), is an aggressive brain tumor primarily occurring in young patients (<4 years of age) and characterized by C19MC amplification and Lin28 overexpression. These genetic hallmarks have been shown to participate in driving ETMR in a C19MC-Lin28-MYCN circuit. Reducing Lin28 disrupts this circuit and reduces cell viability in ETMR models. Investigation of therapeutic agents targeting this pathway is required to provide new treatment options for this deadly disease. We present data showing the effect of DFMO (α-difluoromethylornithine) in ETMR, an ODC1 inhibitor known to reduce Lin28 in neuroblastoma. DFMO treatment of the ETMR cell line BT-183 resulted in a significant reduction of intracellular Lin28 protein levels (P<0.05) as indicated by flow cytometry. In concert with this reduction in Lin28, there was a as significant reduction in viable cells (P<0.05), and the number of CD133+ cells were reduced 2-fold (P<0.05). High throughput drug testing of BT-183 identified a number of additional therapeutic agents with potential therapeutic efficacy for ETMR and combining these with cytostatic agent DFMO demonstrated the potential use of these drugs in combination. These in vitro data were complemented by testing of DFMO in an in vivo stereotaxic xenograft ETMR model, with inhibition of tumor burden monitored by bioluminescent imaging of the tumors. Together this work shows that Lin28 targeting agents such as DFMO merit further examination and integrating these types of agents into treatment strategies for ETMR may lead to better outcomes.